Utilization of palm frond waste in the manufacture of liquid smoke for sustainable agriculture - Sinaga, Novalia Siti Ramadani; Sandria, Feri; Zamzami, Lutfi Fadilah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The utilization of palm frond waste as raw material for liquid smoke production is a sustainable innovation in supporting environmentally friendly agriculture. Palm fronds, which are usually considered waste, have high potential to be processed into liquid smoke through pyrolysis process. Liquid smoke contains organic compounds such as organic acids, phenols, and carbonyl compounds that can be utilized as natural pesticides, organic preservatives, and plant growth stimulants. This study aims to assess the production method, chemical composition, and effectiveness of liquid smoke from palm fronds in agricultural applications. The results showed that liquid smoke can improve soil fertility, reduce the use of synthetic pesticides, and support sustainable agricultural practices. The utilization of palm frond waste as liquid smoke not only provides a solution for plantation waste management, but also contributes to improving the efficiency and sustainability of the agricultural sector.